Предмет: Математика,
автор: dilberibra2009
3 Замените квадратное уравнение равносильным приведённым квадрат- ным уравнением.
Приложения:
Ответы
Автор ответа:
3
Ответ:
Пошаговое объяснение:
а) 3x²+6x-12=0 => делим на 3=>
x²+2x-4=0 - равносильное уравнение.
b) 2x²-10x+12=0 => делим на 2 =>
x²-5x+6=0 - равносильное уравнение.
c) 5x²-4x-1 = 0 => делим на 5=>
x²-4/5x-1/5=0 - равносильное уравнение.
d) -x²+6x+3=0 => умножаем на (-1)=>
x²-6x-3=0 - равносильное уравнение.
Похожие вопросы
Предмет: Математика,
автор: irinakozhuhar09
Предмет: Литература,
автор: seredukulana8
Предмет: Химия,
автор: yalubluinui
Предмет: Информатика,
автор: Noob0101
Предмет: Алгебра,
автор: SanoGoy